The effects of aerobic exercise frequencies on liver fibrosis, alpha-fetoprotein and cytokeratin 19 in experimental type 2 diabetes-induced rats: an immunohistochemistry study - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2018)
We investigated using immunohistochemistry the effects of frequency of aerobic exercise on liver fibrosis and measured the expression of the oval cell marker, alpha fetoprotein (AFP), and the hepatocellular carcinoma marker, CK 19, in rats with early-period induced type 2 diabetes (T2DM). Rats were divided into four groups: control sedentary rats, diabetic sedentary rats, diabetic rats with continuous exercise (30 min/day, 5 days/week) and diabetic rats with short periods of exercise (3 x 10 min/day, 5 days/week). T2DM was induced using an intraperitoneal (i.p.) injection of nicotinamide (NA) and streptozotocin (STZ). Liver samples were obtained 8 weeks after injection. Tissue sections were stained with hematoxylin and eosin, periodic acid-Schiff and Masson's trichrome. We also used immunochemical staining for AFP, smooth muscle actin (alpha-SMA) and CK19. Continuous and short periods of aerobic exercise produced similar effects during the early period of liver damage in the STZ-NA model, i.e., decreased blood glucose levels and improved body weight, improved liver histology and reduced fibrosis, necrosis and steatosis; and reduced expression of AFP and alpha-SMA. Moderate aerobic exercise for 150 min/week appeared to reduce early liver damage in a rat model of T2DM.
Keywords: AFP; CK19; diabetes mellitus; nicotinamide; physical activity; rats; streptozotocin; HEPATOCELLULAR-CARCINOMA; PATHOLOGICAL PROGRESSION; ANTIDIABETIC ACTIVITY; PHYSICAL-ACTIVITY; HEPATIC-FIBROSIS; GLYCEMIC CONTROL; STREPTOZOTOCIN; DISEASE; CANCER; MODEL